Mechanizmy rynkowe i interwencja państwa w polityce regionalnej Chińskiej Republiki Ludowej (Politeja, 2020)
Market Mechanisms and State Intervention in Diversifying the Regional Development of the People’s Republic of ChinaThe article focuses on the importance of market mechanisms and state intervention in the field of regional development policy, in particular on the dominant process of development differentiation. The aim of the article is to verify to what extent market mechanisms are the driving force in China’s regional development policy, and to what extent state intervention is the driving force. It is also important because of the fact that regional policy is an amalgam of the public intervention and presence of market forces, regardless of the country’s political regime. The article identifies the elements that determine the differentiation of regional development due to the operation of market mechanisms and state intervention in China’s regional policy.